Multi Centric Paget's Disease and Review of Literature - Zohreh Yousefi; Marjaneh Farazestanian; Amir Hosein Jafarian; Laya Shirinzadeh; Anahita Hamidi (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Introduction: Paget's disease of the vulva (PDV) is a very rare malignancy originating in vulvar apocrinegland-bearing skin cells. Based on multi centric nature of Paget's disease, it's a chronic and relapsing course. The aim of this report is to introduce a case of multi centric Paget's disease and review of literature. Case report: A 62-year-old woman with complaints of vulvar pruritus, painful vulvar lesion for 4 years was referred to oncology department of Ghaem hospital, Mashhad University of Medical Sciences in 2016. Pathological results of erythematous and exfoliated lesion of the major and minor labia extend to anus was reported as PDV with full-thickness involvement. In investigations, she had persistent hematuria. Pelvis and abdomen investigation revealed irregularity in the posterior wall of the bladder and biopsy detected urothelial carcinoma in the bladder. Radical cystectomy was performed subsequently. In addition, complete response of vulvar lesion to imiquimod cream was seen after 6 weeks of therapy. The patient is free of disease and now she is under serial follow-up.  Conclusion: Generally standard treatment modality in patients who experienced multicenteric Paget's disease is surgical resection, also topical 5% imiquimod cream may be considered as an alternative option in setting metastatic vulvar Paget.